An investigation into the effectiveness of collaboration between Greek secondary EFL teachers and specialist providers for dyslexia issues. Issue 1 (7th June 2011) - Rontou, Maria
<x xml:space="preserve">Abstract</x> This paper investigates the collaboration of Greek secondary school teachers of English as a Foreign Language (EFL) with psychologists and advisers for dyslexia issues. Data were collected through audio recorded observations and interviews with head teachers and teachers. Taking a Vygotskian approach to learning, activity theory is applied to analyse the contradictions that emerge around the collaboration of teachers and head teachers with specialist provision for dyslexia issues from data in interviews and field notes across two schools. The analysis shows that contradictions are created when the participants try to achieve their goals for dyslexia support by the absence of 'what' artefacts – such as knowledge on dyslexia – and 'how' artefacts – processes and procedures such as collaboration with a counsellor – to support the collaboration of EFL teachers with EFL and special educational needs advisers and psychologists, the lack of staff at diagnostic centres and lack of funding for training. This finding indicates that the collaboration between psychologists, advisers and teachers to exchange information on pedagogy needs to be established through meetings and in‐service training of teachers.